2020
DOI: 10.7759/cureus.9289
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Bacteremia in the Setting of a Coronary Artery Fistula

Abstract: We present an interesting case of a 31-year-old female with recurrent Staphylococcus lugdunensis bacteremia in the setting of a coronary artery fistula (CAF). Over the course of several months, the patient was admitted to the hospital on three separate occasions with an unclear source of bacteremia. She suffered from numerous complications, including cavitary pneumonia, osteomyelitis, synovitis and septic emboli. On each admission, the patient received intravenous (IV) antibiotic therapy. CT scan of the chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…4,9 Two cases of S. lugdunensis septic embolism in the absence of IE have been reported. 10,11 Ishidou et al 10 reported a patient underwent prolonged antibiotic therapy for a month but decompensated a month after discontinuation, and the conduit, a polytetrafluoroethylene foreign body, was found to be obstructed during autopsy. Shah et al 11 described the patient underwent multiple antibiotic courses for recurrent bacteremia and finally underwent surgical ligation of a coronary artery fistula, which was presumed to be the source of bacteremia, without any further recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,9 Two cases of S. lugdunensis septic embolism in the absence of IE have been reported. 10,11 Ishidou et al 10 reported a patient underwent prolonged antibiotic therapy for a month but decompensated a month after discontinuation, and the conduit, a polytetrafluoroethylene foreign body, was found to be obstructed during autopsy. Shah et al 11 described the patient underwent multiple antibiotic courses for recurrent bacteremia and finally underwent surgical ligation of a coronary artery fistula, which was presumed to be the source of bacteremia, without any further recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Ishidou et al 10 reported a patient underwent prolonged antibiotic therapy for a month but decompensated a month after discontinuation, and the conduit, a polytetrafluoroethylene foreign body, was found to be obstructed during autopsy. Shah et al 11 described the patient underwent multiple antibiotic courses for recurrent bacteremia and finally underwent surgical ligation of a coronary artery fistula, which was presumed to be the source of bacteremia, without any further recurrence. Both cases illustrate the importance of a combination of medical and surgical intervention when appropriate under close monitoring in patients with S. lugdunensis bacteremia, even in the absence of IE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of CAF range from mild dyspnoea, fatigue, chest discomfort, dizziness, syncope, and angina to severe heart failure, pulmonary congestion and MI, all depending upon the severity of the steal and the shunt pathway. [13][14][15][16] Recent cumulative evidence suggests that fistulas remain asymptomatic in first two decades of life but with advancing age the majority of fistulas become symptomatic, especially in the fifth or sixth decades of life. 13 For age <20 years, only one-fifth of the fistulas are symptomatic, while more than two-thirds of the fistulas are symptomatic after the age of 60 years.…”
Section: Clinical Importance and Consequencesmentioning
confidence: 99%